Transmission of U.S. Tariff Shocks and Macroeconomic Adjustments in the U.K. Economy - Jackson, Emerson Abraham (Theoretical and Practical Research in Economic Fields, 2025)
This paper examines the transmission of tariff-induced price shocks from the United States to the United Kingdom, focusing on sectoral cost pass-through, inflationary dynamics, and macroeconomic adjustment. Employing a difference-in-differences specification and local-projection impulse-response analysis, the study quantifies the extent to which tariffs on metal-intensive imports affected U.K. producer prices, consumer inflation, and real output. Empirical findings show that a 10 percent increase in tariff exposure raises producer prices by approximately 4.5 per cent, while a temporary Tariff Rate Quota (TRQ) arrangement between 2022 and 2024 alleviated cost pressures. The dynamic responses reveal a short-run contraction in real GDP growth of about 0.3 percentage points, peaking after four to six quarters and dissipating within two years. These findings confirm that tariff shocks transmit primarily through supply-cost and exchange-rate channels rather than demand-side mechanisms. Robustness checks using alternative model specifications, placebo timings, and clustered-error adjustments confirm the stability of the results. The study contributes to current debates on trade protection and imported inflation (Amiti, Redding, & Weinstein, 2019; IMF, 2023; OECD, 2024), offering insights into the resilience of open economies under renewed protectionist pressures.